Cohomologie, stabilisation et changement de base - Labesse Jean-Pierre (Paris Societie Mathematique de France, 1999)
This volume introduces the concept of a crossed set'' (a generalization of crossed modules) and studies the Galois cohomology of these objects. This is the key to the stabilization of all elliptic terms for the twisted trace formula. It proves the exis
Keywords: Crossed modules; Galois cohomology